Prompt release of vesel and crew under article 292 of the UNCLOS: Is It An adequate safeguard against the powers of coastal states? - Hamid, Abdul Ghafur@Khin Maung Sein (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
The enforcement powers of the coastal State over foreign vessels in their territorial seas normally include arrest of the crew, seizure of the vessels, and their detention that may extend for a considerable length of time. What makes the matter worst is the extension by the UNCLOS 1982 of the coastal State’s powers to the new legal regime of the exclusive economic zone that may extend up to 200 nautical miles from the baselines. These extensive enforcement powers of the coastal States may cause hardship to foreign crew and ship owners. To strike a balance between the interests of the coastal State and those of the flag State, Article 292 of the UNCLOS empowers the International Tribunal for the Law of the Sea (ITLOS) to determine whether or not the detaining State has complied with a provision of the Convention for the prompt release of the vessel or the crew upon the posting of a reasonable bond or other financial security. The main objective of the research, therefore, is to examine whether the overriding purpose of Article 292, that is, to serve as a compromise between the conflicting interests of the coastal and the flag States, is achieved. The methodology is primarily based on analysis of the nine prompt release cases filed before the ITLOS to date, exploring how Article 292 is in fact interpreted and applied by the Tribunal. The study concludes that despite the prompt release obligation, the coastal States naturally are in a position to tip the balance in their favour. The absence of direct access of private persons to the prompt release procedure and the tendency of the coastal State to confiscate the detained vessel are found to be the two main factors that may swing the balance towards the coastal State.